Fotografia e aderência simbólica: “aura”, “engajamento” e “memória” no protagonismo fotográfico - Maria da Conceição Francisca Pires (Universidade do Vale do Rio dos Sinos (UNISINOS), 2016)
Based on the works of Barthes (1980), Benjamin (1996), Bourdieu (1979) and Halbwachs (1990), we discuss the elements that favored that the photographs “Migrant Mother” (by Dorothea Lange, 1936) and “The Death of the Militiaman” (by Robert Capa, 1936) were incorporated into a collective imaginary, becoming the reference of a certain historical reality. We understand that these images have in common the relationship they established with the memories and experiences of the societies they represent and that they create for the audience a visual narrative about the lived experience. They influence their social and political dynamics in the public sphere, as well as favoring a reflection about the photographic act, concerning its technical work and its political character.